Contribution of the endosteal surface of cortical bone to the trabecular pattern seen on IOPA radiographs: an in vitro study - P T Ravikumar; R Thiruneervannan Thiru; K S Ganapathy; Padmavathy Padma; Ramesh Vellingiri; Senthil (Wolters Kluwer Medknow Publications, 2012)
Objectives: A study was conducted to assess the contribution of the cancellous and endosteal surface of the cortical bone to the trabecular pattern seen in an IOPA radiograph. Materials and methods: An in vitro study analyzing the contribution of the endosteal surface of cortical bone and cancellous bone to the trabecular pattern was conducted, using 60 specimens of desiccated human mandibles. The mode of execution involved IOPA radiographic evaluation of premolarmolar segments in the specimens before and after removal of cancellous bone. The radiographs were numbered for identification and subjected to evaluation by 5 dentomaxillofacial radiologists who were doubleblinded to ensure an unbiased interpretation. Results: The trabecular pattern appreciation by the experts in the IOPA radiographs before and after removal of cancellous bone displayed immaculate correlation as per the Goodman-Kruskal Gamma Coefficient values which was 0.78 indicating a very large correlation. The relative density of trabecular pattern was significantly higher in radiograph before than after removal of cancellous bone with p-value less than 0.05. Conclusion: Based on these results it was adjudged that both the cancellous and endosteal surface of cortical bone contributed significantly to the trabecular pattern in an IOPA radiograph.